2011
DOI: 10.1111/j.1744-7976.2010.01193.x
|View full text |Cite
|
Sign up to set email alerts
|

The Economics of Wetland Drainage and Retention in Saskatchewan

Abstract: The public and private net benefits of retaining wetlands in agricultural cropland in east central Saskatchewan are evaluated in a policy case study. Wetland drainage on agricultural lands continues to occur despite evidence from existing studies concerning societal benefits derived from wetland retention. A simulation model was developed to estimate on‐farm costs and benefits associated with wetland drainage in east central Saskatchewan. The private net benefits were compared to existing estimates of the publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
48
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 11 publications
0
48
3
Order By: Relevance
“…Surface and subsurface drainage remains an economically beneficial, yet largely unregulated land management practice in the Midwestern USA and Canada that affects enormous swaths of agricultural land (Cortus et al, 2011). Drainage 10 data reported by USDA Census of Agriculture, indicate that the Minnesota River basin and Illinois River basin are most extensively drained (at least 42%-45% of the watershed area), have seen an increase in drainage activity since 1940, and that the majority of drainage in these basins today is subsurface tiling.…”
Section: Interpretations Implications and Conclusionmentioning
confidence: 99%
“…Surface and subsurface drainage remains an economically beneficial, yet largely unregulated land management practice in the Midwestern USA and Canada that affects enormous swaths of agricultural land (Cortus et al, 2011). Drainage 10 data reported by USDA Census of Agriculture, indicate that the Minnesota River basin and Illinois River basin are most extensively drained (at least 42%-45% of the watershed area), have seen an increase in drainage activity since 1940, and that the majority of drainage in these basins today is subsurface tiling.…”
Section: Interpretations Implications and Conclusionmentioning
confidence: 99%
“…The economic incentives to drain and convert wetlands have generally increased as technological changes have decreased the mechanical costs of draining wetlands while larger agricultural equipment has increased the private costs of field obstructions, including wetlands (De Laporte, 2014). Cortus et al (2011) reported that the reduction or elimination of in-field nuisance cost imposed by wetlands located in annual crop fields contributed approximately 35% of the private benefits achieved from draining wetlands. Wetland drainage on existing lands is a profitable management practice since, from the perspective of the farmer, wetlands provide insufficient or no significant direct financial benefit (De Laporte, 2014;Cortus et al, 2011).…”
Section: Introductionmentioning
confidence: 98%
“…Cortus et al (2011) reported that the reduction or elimination of in-field nuisance cost imposed by wetlands located in annual crop fields contributed approximately 35% of the private benefits achieved from draining wetlands. Wetland drainage on existing lands is a profitable management practice since, from the perspective of the farmer, wetlands provide insufficient or no significant direct financial benefit (De Laporte, 2014;Cortus et al, 2011). Therefore, on privately owned agricultural land, policy measures that encourage the adoption of land management that decreases private net benefits to meet an objective of increasing social net benefits requires positive, often monetary, incentives (Pannell, 2008;Brown et al, 2007).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Surface and subsurface drainage remains largely unregulated throughout the Midwestern USA and Canada (Cortus et al, 2011). Drainage census data are prone to reporting inconsistencies and errors, overall underestimation of drainage from excluding farms less than 500 acres, and do not provide the information necessary for modeling basin hydrology in large agricultural watersheds (such as drain size, depth, spacing, and extent).…”
Section: Interpretations Implications and Conclusionmentioning
confidence: 99%